2016
DOI: 10.1016/j.brat.2015.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Supervision for treatment of depression: An experimental study of the role of therapist gender and anxiety

Abstract: Article available under the terms of the CC-BY-NC-ND licence (https://creativecommons.org/licenses/by-nc-nd/4.0/) eprints@whiterose.ac.uk https://eprints.whiterose.ac.uk/ Reuse Unless indicated otherwise, fulltext items are protected by copyright with all rights reserved. The copyright exception in section 29 of the Copyright, Designs and Patents Act 1988 allows the making of a single copy solely for the purpose of non-commercial research or private study within the limits of fair dealing. The publisher or oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 36 publications
0
6
0
1
Order By: Relevance
“…There is also growing evidence for the association between supervision and better outcomes for both clinicians and their clients (Rakovshik et al, 2016). However, the sparse previous studies on the effect on therapist behaviour and client outcome shows ambiguous results (Simpson-Southward et al, 2016;Zarbock et al, 2009), and the methodological shortcomings of this research make it difficult to identify the specific supervision features that constitute best practices (Bearman et al, 2017). In recent years, there has been an increased focus on ensuring supervisor competence and effective supervision practice in both evidence-based clinical supervision (Milne and Reiser, 2012) and competency-based supervision (Falender and Shafranske, 2007).…”
Section: Clinical Supervisionmentioning
confidence: 99%
“…There is also growing evidence for the association between supervision and better outcomes for both clinicians and their clients (Rakovshik et al, 2016). However, the sparse previous studies on the effect on therapist behaviour and client outcome shows ambiguous results (Simpson-Southward et al, 2016;Zarbock et al, 2009), and the methodological shortcomings of this research make it difficult to identify the specific supervision features that constitute best practices (Bearman et al, 2017). In recent years, there has been an increased focus on ensuring supervisor competence and effective supervision practice in both evidence-based clinical supervision (Milne and Reiser, 2012) and competency-based supervision (Falender and Shafranske, 2007).…”
Section: Clinical Supervisionmentioning
confidence: 99%
“…Clinical supervision has been suggested to have a positive effect on clinical outcomes, but the results of published studies are not consistent: for example, Bambling et al (2006) reported a positive effect on patient outcomes, whereas White & Winstanley (2010) reported no significant effects. One of the few studies to have examined the effect of clinical supervision on therapists’ delivery of CBT to patients with depression found that the therapists’ gender and their anxiety levels both influenced the supervisors’ focus in supervision, suggesting that supervisors show biases in the way they support the work of different clinicians (Simpson-Southward 2016). Thus, there is a need to increase our understanding of the potential effect of clinical supervision on treatment effectiveness and drop-out rates in cognitive therapy and CBT.…”
Section: Reducing Drop-out Rates and Improving Outcomesmentioning
confidence: 99%
“…CBT therapists who received more supervision or had greater levels of self-esteem were more likely to use these non-CBT techniques. These findings might imply that supervisory drift is occurring (Simpson-Southward et al, 2016;Simpson-Southward et al, 2017), and that therapists have greater self-belief and do not see as strong a need to focus on evidence-based approaches.…”
Section: Discussionmentioning
confidence: 98%